Effect of long-term acid attack on impermeability and microstructure of compacted cement-bound soils - Dong, Zhiwei (Environmental technology, 2023)
Compacted cement-bound soils (CCS) are widely used as leakage barriers around solid waste landfills and contaminated sites. However, a study of its long-term reliability in an acidic environment is relatively scarce. A 3-year-long experimental study on the changes in permeability coefficient and microstructure of CCS under acid attack was conducted, from which the following conclusions can be drawn: the permeability coefficient of CCS under weak acid (pH = 5.00) attack decreased progressively with time, from 4.90 × 10-8 cm/s at the beginning to 6.70 × 10-10 cm/s after 3 years. Under strongly acidic environments with pH values of 2.65 and 3.65, the permeability coefficients of CCS initially decreased and then increased with time, reaching 6.70 × 10-5 and 9.37 × 10-8 cm/s, respectively. The degradation effect of a weak acid (pH = 5.00) on the hydration products of cement was mild as a large amount of hydration products (e.g. C-S-H shaped in short fibrous) remained in the pores of CCS after 3 years of immersion. However, strong acid caused an obvious degradation effect on the hydration products, which almost disappeared after 3 years of immersion. Based on the study data, a unified mathematical model was developed to correlate the permeability coefficient of CCS, immersion time and acidic solution pH value. Furthermore, a quantitative expression function between the service life of CCS and solution pH value was established